Characterization and clinical implications of peripheral arterial involvement in transthyretin cardiac amyloidosis cardiomyopathy. (25th November 2020) - Stamatelopoulos, K; Delialis, D; Bampatsias, D; Tselegkidi, M.E; Petropoulos, I; Roussou, M; Gavriatopoulou, M; Aivalioti, E; Patras, R; Pamboucas, C; Kanakakis, I; Terpos, E; et al.
Abstract: Background: The sporadic form of transthyretin amyloidosis cardiomyopathy (ATTR-CM) is underdiagnosed but its prevalence is increasing due to the aging population. Given the poor prognosis of ATTR-CM understanding the underlying pathophysiologic mechanisms of the disease is imperative in order to improve strategies for early diagnosis and risk stratification and to develop new effective therapeutic options. ATTR-CM is associated with hypotension and there is preliminary experimental evidence of vascular involvement but its presence and clinical significance remains unknown. Purpose: To characterize peripheral arterial involvement and explore its clinical role in ATTR-CM. Methods: We consecutively recruited 28 previously untreated patients with newly diagnosed ATTR-CM and 34 elderly controls >70 years old, without ATTR-CM or heart failure. In both groups, flow-mediated dilatation (FMD) and intima-media thickness (IMT) in the carotid arteries were measured by high-resolution ultrasonography as markers of peripheral vascular reactivity and of subclinical atherosclerosis, respectively. Carotid-femoral pulse wave velocity (PWV) was measured as a marker of arterial stiffness. Aortic blood pressure (BP) and augmentation index (AI) using applanation tonometry were measured as markers of arterial wave reflections, peripheral arterial resistance and central hemodynamics. Echocardiography was performed in all ATTR patients. All cardiovascular (CV) measurements were performed before administration of any ATTR-specific therapy. Results: ATTR patients were older and had lower prevalence of hypertension and male gender (p<0.05 for all) than the control group. Aortic and peripheral BP (p=0.016–0.088) and AI (p=0.003) were lower in ATTR patients. IMT in the common (cc) and internal carotid (ic) as well as in the carotid bulb (cb) were significantly higher in ATTR patients (p=0.001–0.042). After multivariable adjustment for traditional CV disease (CVD) risk factors, the ATTR group was independently associated with AI and IMT in cc, cb and ic (p<0.05 for all). In a subgroup of subjects with similar age between groups (n=13 and n=33 and 74.5±2.9 vs. 75.6±3.6 years, for ATTR vs. controls, respectively) differences in AI and cbIMT remained significant. Interestingly, AI was strongly and inversely associated with interventricular wall thickness (IVwt) in ATTR patients (spearman rho=−0.651, p=0.001). After adjustment for traditional CVD risk factors this association remained significant. Conclusion: ATTR-CM is associated with lower aortic wave reflections, which correlate with more advanced structural cardiac disease, as assessed by IVwt. Further, ATTR-CM patients present accelerated subclinical carotid atherosclerosis as compared to elderly control subjects. These findings suggest that in ATTR-CM there is disease-specific peripheral vascular involvement in parallel to cardiac involvement. The clinical significance of these findings merits further investigation. Funding Acknowledgement: Type of funding source: None